Implementation of Gender Mainstreaming (PUG) through Gender-Responsive Planning and Budgeting (PPRG) in Medan City - Daulay, Mutiara; Siahaan, Asima Yanty Sylvania (LPPM Universitas Jambi, 2026)
Gender mainstreaming (GM) through Gender-Responsive Planning and Budgeting (GRPB) is a strategic policy instrument for promoting gender equality in regional development, including in Medan City, Indonesia. This study examines the implementation of GM through GRPB in Medan City using a descriptive qualitative approach. Data were collected through observations, in-depth interviews, documentation, and literature review at the Department of Women’s Empowerment, Child Protection, Community Empowerment, Population Control, and Family Planning (DP3APMPPKB) of Medan City. Informants included officials responsible for gender mainstreaming, program formulation, and regional planning. Data were analyzed using Edwards III’s policy implementation framework, focusing on communication, resources, implementers’ disposition, and bureaucratic structure. The findings indicate that GRPB has been integrated into the planning process across regional government agencies by incorporating evaluations of previous gender-related programs. However, implementation remains constrained by limited communication following budget adjustments, insufficient financial and infrastructural resources, varying levels of commitment among implementers, and the incomplete establishment of the Gender Mainstreaming Focal Point, which weakens coordination and institutional accountability. These challenges reduce the effectiveness of GRPB in achieving gender equality objectives. The study concludes that strengthening regulatory support, enhancing institutional capacity, improving inter-agency coordination, and ensuring sustained political commitment are essential for optimizing GRPB implementation and advancing gender-responsive development in Medan City.